2008
DOI: 10.1002/ar.20755
|View full text |Cite
|
Sign up to set email alerts
|

Preproenkephalin mRNA is Expressed in a Subpopulation of GABAergic Neurons in the Spinal Dorsal Horn of the GAD67‐GFP Knock‐In Mouse

Abstract: GABA (gamma-aminobutyric acid)ergic neurons in the spinal dorsal horn have been reported to be divided into distinctive populations, with different cotransmitters and neuropeptides. In this study, we examined the colocalization of enkephalin (ENK) mRNA with GABA in the spinal dorsal horn using the glutamic acid decarboxylase (GAD)(67)-green fluorescence protein (GFP) knock-in mouse. Our approach was to perform in situ hybridization histochemistry to detect mRNA for preproenkephalin (PPE, the precursor protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Because naloxone and LY341495 were both administered systemically, it is impossible to determine their site of action. However, it is likely that these drugs interact at least in part at synapses in the lumbosacral spinal cord on the basis of the following observations: 1) group II mGluR and opioid receptors are expressed in the spinal dorsal horn (6,8,21,22,32,41); 2) intrathecal administration of group II mGluR agonists suppress nociceptive behavior (13,23,24,34); 3) AAinduced bladder overactivity is mediated by a reflex pathway organized in the spinal cord (17); 4) our previous study (39) suggested that TNS inhibition of AA-induced bladder overactivity could be mediated by suppression of transmission at a spinal interneuronal synapse prior to the sacral parasympathetic preganglionic neurons; and 5) spinal opioid receptors have a prominent inhibitory effect on micturition (12,20,42,43). Figure 6 shows a hypothetical spinal mechanism for TNS inhibition, which is intended to facilitate the discussion about possible sites of interaction between naloxone and LY341495.…”
Section: Discussionmentioning
confidence: 99%
“…Because naloxone and LY341495 were both administered systemically, it is impossible to determine their site of action. However, it is likely that these drugs interact at least in part at synapses in the lumbosacral spinal cord on the basis of the following observations: 1) group II mGluR and opioid receptors are expressed in the spinal dorsal horn (6,8,21,22,32,41); 2) intrathecal administration of group II mGluR agonists suppress nociceptive behavior (13,23,24,34); 3) AAinduced bladder overactivity is mediated by a reflex pathway organized in the spinal cord (17); 4) our previous study (39) suggested that TNS inhibition of AA-induced bladder overactivity could be mediated by suppression of transmission at a spinal interneuronal synapse prior to the sacral parasympathetic preganglionic neurons; and 5) spinal opioid receptors have a prominent inhibitory effect on micturition (12,20,42,43). Figure 6 shows a hypothetical spinal mechanism for TNS inhibition, which is intended to facilitate the discussion about possible sites of interaction between naloxone and LY341495.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for in situ hybridization were based on previously described procedures (21). Sense and antisense RNA probes (nucleotides 88-377, GenBank NM_002985) were synthesized and labeled with a digoxigenin labeling kit (Roche Diagnostics, Mannheim, Germany).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…To better understand the role of ENK, it is necessary to know the evolution of the population of ENKergic neurons during the course of development. A wealth of data pointed out that in adulthood, spinal ENKergic neurons exist mainly in the superficial laminae [Bennett et al, 1982;Huang et al, 2008a] and play an important role in the transmission and modulation of nociceptive information [Basbaum and Fields, 1984]. However, developmental studies of ENKergic neurons in the mouse spinal cord are scant.…”
Section: Introductionmentioning
confidence: 99%
“…Although the distribution of PPE mRNA has been reported in the mouse developing spinal cord [Xu et al, 2008;Huang et al, 2008b], the appearance of the ENKergic system has not been systematically described. Moreover, even though ENK and ␥ -aminobutyric acid (GABA) have been described as colocalized in neuronal cells of the adult spinal cord [Todd et al, 1992;Huang et al, 2008a], such information is missing, especially during the course of development.…”
Section: Introductionmentioning
confidence: 99%